Formulation of poly(butylene adipate-co-terephthalate)/caffeic acid composites for vegetable packaging applications - Sana, Siva Sankar (2025)
Poly(butylene adipate-co-terephthalate) (PBAT) is widely used as a bioplastic owing to its commendable water-barrier properties. In this work, PBAT was blended with caffeic acid (CA) (1–3 wt%) by solution mixing using chloroform as a solvent through solvent casting method. UV–Visible spectroscopy results show a decrease in transmittance from 100 % in PBAT to 6 % PBAT/3CA. The film's elongation was notably improved with an increase in the CA ratio, reaching up to 1055.4 %. Moreover, the tensile strength experienced a significant enhancement upon the inclusion of CA (3 wt%) up to 25.5 MPa. The decrease in water vapor permeability (WVP) (3.05 ± 0.1 × 10−11 g.m/m2.Pa.s) and water contact angle (WCA) (60.5° ± 1.34°) was observed in PBAT/3CA. PBAT film containing 3 wt% CA exhibited remarkable scavenging action against ABTS•+ and DPPH•, recording values of 100 % and 98.5 %, respectively. When subjected to testing against foodborne pathogens such as Escherichia coli (E. coli) and Listeria monocytogenes (L. monocytogenes), the fabricated films displayed excellent antibacterial activity. The active films comprising PBAT/CA possess the potential to serve as a synergistic solution for food packaging, combining the UV barrier property, mechanical properties, flexibility, peeling resistance, and renowned biodegradability of PBAT with the ability to repurpose industrial waste.